Measurement of Join Patch Properties and Their Integration into Finite-Element Calculations of Assembled Structures - A. Schmidt; S. Bograd; L. Gaul (Shock and Vibration)
The vibration and damping characteristics of an assembled structure made of steel are investigated by an experimental modal analysis and compared with the results of a finite element modal analysis. A generic experiment is carried out to evaluate the stiffness and the damping properties of the structure's join patches. Using these results, an appropriate finite element model of the structure is developed where the join patches are represented by thin-layer elements containing material properties which are derived from the generic experiment's results. The joint's stiffness is modeled by orthotropic material behavior whereas the damping properties are represented by the model of constant hysteresis, leading to a complex-valued stiffness matrix. A comparison between the experimental and the numerical modal analysis shows good agreement. A more detailed damping model in conjunction with an optimization procedure for the joint's parameters results in an improved correlation between the experimental and the numerical modal quantities and reveals that the results of the generic experiment are sound.